Employment law - Ali Mohamed, Ashgar Ali; Ahmad, Muhamad Hassan; Masum, Ahmad; Arowosaiye, Yusuf Ibrahim; Lilienthal, Gary (LexisNexis Malaysia Sdn Bhd, 2025)
Generally, a worker has an economic interest in retaining the job for as long as he is capable of doing so or until the age of retirement. A worker’s job security is recognised in Malaysia to the extent that the courts have given a liberal interpretation to the word ‘life’ in article 5(1) of the Federal Constitution to include the right to livelihood. Various statutes have been enacted in Malaysia to protect workers by regulating working conditions, providing various benefits to the workers apart from prohibiting arbitrary dismissal from employment. This is unlike the utilitarian philosophy of Bentham which introduced the doctrine of laissez-faire which doctrine is still prevalent at common law that the employee has no job security and that his services may be terminated with appropriate notice of termination as per the employment contract or the implied reasonable notice. Hence, the move by the legislature to enact employment statute such as the Industrial Relations Act 1967 (Act 177) (‘IRA 1967’) which does not condone, for example, arbitrary termination of an employee irrespective of whether he is engaged in employment on a permanent or probational basis. Having said the above, this chapter discusses the relevant labour statutes in Malaysia as well their application to an employee under a contract of service or a contract of employment. The discussion would also encompass the settlement of labour disputes with reference to the jurisdiction of the Industrial Court and the ‘Labour Court’.